Law, justice and social change - Saxena ,D.R.; Saxena, D. R., 1943- (New Delhi : Deep & Deep Publications, 1996)
Contributed articles.
Includes bibliographical references and index.
Keywords: Justice, Administration of -- India; Social change -- India